Factors Driving Souvenir Purchase in Bangkok from Japanese Tourists’ Expectation - Witchayakawin, Pakin (วารสารวิชาการการท่องเที่ยวไทยนานาชาติ, 2016)
This research aims to identify factors driving souvenir purchasing in Bangkok from Japanese tourists’ expectation. Only inbound Japanese visitors in several places of Bangkok were targeted for the questionnaires collection. The weight of choice formula is used for finding the rank of shopping elements 1 to 5 among 15 elements. The findings reveal Japanese tourists to expect reasonable goods price, Thainess (Thai style), convenient traveling, a friendly touch of Thai people and good quality with inexpensive price, respectively.